Mapeamento geológico e petrografia do alvo T-578 - Greenstone Belt Pilar de Goiás (Pilar de Goiás - GO) - Donato, Fábio Tosi di [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The study area is located in the geological parameters of the Pilar de Goiás Greenstone Belt (GO), it is part of the Pilar de Goias Group’s meta-volcano-sedimentary sequence. This is a homoclinal package constituted by terrigenous metassediments containing intercalations of meta-ultramafic rocks and iron formations. The units that were informally named in this work, are interpreted as belongs to the Serra do Moinho Formation. Through mineralogical associations the area’s metamorphism were classified as high greenschist facies garnet zone. Prior to this work were detected in the area, through soil samples, some auriferous anomalies. One of the objectives of this work is the detection of possibles hidrotermal alterations related to these anomalies presents in the study area

A área de estudo localiza-se no contexto geológico do greenstone belt Pilar de Goiás (GO), fazendo parte das sequência meta-vulcanossedimentar do Grupo Pilar de Goiás. Trata-se de um pacote homoclinal de metassedimentos terrígenos contendo intercalações de rochas meta-ultramáficas e formações ferríferas. As unidades informalmente nomeadas nesse trabalho foram interpretadas como sendo pertencentes a Formação Serra do Moinho. Através das associações mineralógicas atribuiu-se o metamorfismo da área como sendo de fácies xisto verde alto zona da granada. Previamente a este trabalho foram detectadas na área algumas anomalias auríferas através de amostras de solo, sendo um dos objetivos desse trabalho a detectação de possíveis alterações hidrotermais relacionadas a essas anomalias presentes na área de estudo
Keywords: Mapeamento geologico; Petrologia; Alteração hidrotermal; Facies (Geologia); Geologia estrutural; Pilar de Goiás (GO); Greenstone belts; Geological mapping; Petrology; Hydrothermal alteration; Facies (Geology); Geology, Structural